‘VASPFix’ for measurement of VASP phosphorylation in platelets and for monitoring effects of P2Y12 antagonists - Glenn, Jacqueline R.; Dovlatova, Natalia; White, Ann E.; Dhillon, Kiren; Heptinstall, Stan; Fox, Susan C. (Thrombosis and Haemostasis, 2014)
Vasodilator-stimulated phosphoprotein (VASP) is phosphorylated and dephosphorylated consequent to increases and decreases in cyclic nucleotide levels. Monitoring changes in VASP phosphorylation is an established method for indirect measurement of cyclic nucleotides. Here we describe the use of an innovative cocktail, VASPFix, which allows sensitive and reproducible measurement of phosphorylated VASP (VASP-P) in a simple, single-step procedure using cytometric bead technology. Frozen VASPFix-treated samples are stable for at least six months prior to analysis. We successfully used VASPFix to measure VASP-P in platelets in both platelet-rich plasma and blood in response to compounds that increase (dibutyryl cAMP, adenosine, iloprost, PGE1) and decrease (ADP, PGE1) cAMP, and to determine the effects of certain receptor antagonists on the results obtained. The change in VASP-P brought about by adding ADP to PGE1-stimulated platelets is a combination of the effect of ADP at the P2Y12 receptor and of PGE1 at both IP and EP3 receptors. For iloprost-stimulated platelets EP3 receptors are not involved. A procedure in which iloprost, ADP and VASPFix were used to determine effectiveness of clopidogrel and prasugrel in patients was compared with an established commercial procedure that uses PGE1 and ADP; the latter produced higher platelet reactivity values that were the result of PGE1 interacting with platelet EP3 receptors. We conclude that VASPFix can be used both as a research tool and for clinical investigations and provides better specificity for P2Y12 receptor inhibition. The latter confers a distinct advantage over existing methods used to monitor effects of P2Y12 antagonists on platelet function.
Keywords: VASP phosphorylation; cyclic nucleotides; cytometric bead assay; P2Y12 antagonists; platelets